A survey on performance analysis of energy aware multicast routing protocols in mobile ad hoc network. (1st January 2014) - Subramaniam, Mahendrakumar; Ramasamy, Sasikala
A mobile ad hoc network (MANET) is a self-configuring infrastructure less network of mobile devices communicating with each other through wireless links. Multicasting in MANET is going to play a key role in future wireless network. For resource limited environment like MANET, it is necessary to minimise energy utilisation of a network and also providing effective communication. Several energy efficient multicast routing protocols have been proposed in recent years for possible deployment of MANETs in government, military and business applications. In this paper, we present a thorough survey on performance analysis of various energy aware multicast routing protocols in mobile ad hoc network. A general overview has been given on multicast routing protocols, describing how they work, their advantages, limitations and their future enhancements. Finally, comparisons are made among various multicast routing protocols considering parameters like energy aware, topology, location aware, robustness, QoS aware, initialisation, control overhead and periodic control messaging, scalability etc.